Da'wah of Betawi Scholars in the Development of Islamic Society in the 19th-21st Century - Sarbini Anim (CV. Syntax Corporation Indonesia, 2023)
Ulama Betawi in the 19th to 21st centuries played an important role in the development of the Muslim community in Jakarta. They helped spread Islam through education and preaching, as well as playing an active role in the formation of religious organizations. In addition, they also played a role in the economic development of the Muslim community through entrepreneurship and economic empowerment. The contribution of the Ulama Betawi was an important factor in the development of the Muslim community in Jakarta during that period. The Ulama Betawi also played a role in maintaining the unity of the Muslim community in Jakarta. They often served as guides in solving social problems that occurred among Muslim communities, such as family, economic, and other social issues. They also played a role in preserving the traditions and culture of Betawi that developed among the Muslim community in Jakarta. The Ulama Betawi realized that Betawi traditions and culture were an integral part of the identity of the Muslim community in Jakarta and as one of the cultural treasures that needed to be preserved. This research uses a qualitative method with a historical approach to understand the concept of dakwah and the role of the Ulama Betawi in the development of the Muslim community in Jakarta in the 19th to 21st centuries. Data was obtained from various sources such as literature, archives, historical documents, and interviews with Ulama Betawi figures. A historical approach was used to describe the development of dakwah and the development of the Muslim community in the past. The results showed that the Ulama Betawi played an important role in the development of the Muslim community in Jakarta through dakwah and socio-economic development strategies. This method provides a holistic perspective and can provide inspiration for the development of dakwah and the Muslim community in the future. The contribution of the Ulama Betawi in the development of the Muslim community in Jakarta in the 19th to 21st centuries was significant. They played an important role in spreading Islam, maintaining the unity of the community, and preserving the culture and traditions of Betawi that developed among the Muslim community.